Agenda jornalística de saúde no Jornal Nacional: avaliação de qualidade e proposta de gestão editorial com base no critério de relevância - Santos, Maria Sol Silva (2019)
The main objective of this study is to experimentally evaluate the journalistic quality of health news published in Jornal Nacional, based on the relevance criterion. The guiding questions of this research are: What is the quality of the journalistic health agenda in Jornal Nacional? And how to measure it systematically, based on the parameter of journalistic relevance, in order to produce a diagnosis of coverage? This study is theoretically based on Journalism by discussing quality and relevance in the field of Communication and Health, through understanding public health in Brazil and the health conditions and indicators of Brazilians. The methodological design was experimental and was made by comparing the governmental, public and journalistic agendas, observing the relevance occupied by the main health topics. The results indicated a journalistic coverage of health classified as poor, since it presented a distance from the reference agendas, represented by the tendency to invisibility of more than half of the topics identified as relevant. The editorial management of journalistic coverage is proposed in this paper through the Journalistic Agenda Guide (GAJ), a methodology still under development, which proportionally operationalizes the relationship between the relevance of the topic and the amount of news articles that must be conditioned. the production capacity of the organization.